Symbiodinium (Dinophyceae) diversity in reef‐invertebrates along an offshore to inshore reef gradient near Lizard Island, Great Barrier Reef. Issue 3 (6th May 2014) - Tonk, Linda; Sampayo, Eugenia M.; LaJeunesse, Todd C.; Schrameyer, Verena; Hoegh‐Guldberg, Ove; Mock, T.
<x xml:space="preserve">Abstract</x> Despite extensive work on the genetic diversity of reef invertebrate‐dinoflagellate symbioses on the Great Barrier Reef (GBR; Australia), large information gaps exist from northern and inshore regions. Therefore, a broad survey was done comparing the community of inshore, mid‐shelf and outer reefs at the latitude of Lizard Island. Symbiodinium (Freudenthal) diversity was characterized using denaturing gradient gel electrophoresis fingerprinting and sequencing of the ITS2 region of the ribosomal DNA. Thirty‐nine distinct Symbiodinium types were identified from four subgeneric clades (B, C, D, and G). Several Symbiodinium types originally characterized from the Indian Ocean were discovered as well as eight novel types (C1kk, C1LL, C3nn, C26b, C161a, C162, C165, C166). Multivariate analyses on the Symbiodinium species diversity data showed a strong link with host identity, consistent with previous findings. Of the four environmental variables tested, mean austral winter sea surface temperature (SST) influenced Symbiodinium distribution across shelves most significantly. A similar result was found when the analysis was performed on Symbiodinium diversity data of genera with an open symbiont transmission mode separately with chl a and PAR explaining additional variation. This study underscores the importance of SST and water quality related variables as factors driving Symbiodinium distribution on cross‐shelf scales. Furthermore, this study expands our knowledge on Symbiodinium species diversity, ecological partitioning (including host‐specificity) and geographic ranges across the GBR. The accelerating rate of environmental change experienced by coral reef ecosystems emphasizes the need to comprehend the full complexity of cnidarian symbioses, including the biotic and abiotic factors that shape their current distributions.